Analisis Faktor Penyebab Komplain Pasien pada Pelayanan Rawat Inap: Studi Kasus di Rumah Sakit X Tahun 2024 - Manzilah, Tasmiati; Hartono, Risky Kusuma (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2025)
Complaints from patients are often used as an indicator of the quality of health services. The causes of complaints from inpatients are related to factors that cause dissatisfaction or discomfort experienced by patients during their hospitalization. This study aims to see the causes of patient complaints about inpatient services. In addition, researchers also examine the relationship between several variables and complaints and analyze further to determine the main factors causing complaints from patients about inpatient services. This study uses a sequential explanatory approach. The study design is cross-sectional for inpatients at Hospital X who are willing to be respondents and provide their perceptions of inpatient services. The factors of inpatient services that are assessed are facilities, human resources, cleanliness, officers' responsiveness, and information availability. Bivariate and multivariate analyses show that these factors have a significant relationship with the level of patient complaints. Patients with a length of stay of more than four days, non-surgical patients, and those who give poor ratings to human resources, facilities, cleanliness, and responsiveness are more likely to complain about hospital services. Hospitals need to implement strategic steps to improve various aspects, such as reducing complaints and improving the quality of service. One effort can be made to provide a spreadsheet link or Google Drive link containing a flow for accelerating complaint handling. Another effort is to implement a comprehensive improvement strategy to improve the patient experience during treatment.